2020
DOI: 10.3389/fphar.2020.552102
|View full text |Cite
|
Sign up to set email alerts
|

Use of Proton Pump Inhibitors in Hungary: Mixed-Method Study to Reveal Scale and Characteristics

Abstract: Background: Due to their efficacy and tolerability, utilization of proton pump inhibitors (PPI) has significantly increased worldwide. Parallel to the clinical benefits, potential longterm side effects have been observed, which, along with increasing medical expenses and potential drug interactions, justifies the analysis of the trends of utilization. Objective: The aim of the present study was to show the level, pattern, and characteristics of PPI use. Methods: We assessed the nationwide use of proton pump in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
3
16
1
1
Order By: Relevance
“…Several studies worldwide have reported a trend of overuse of PPIs [27][28][29][30][31]. A similar pattern has been observed in Saudi Arabia [32,33].…”
Section: Discussionsupporting
confidence: 63%
“…Several studies worldwide have reported a trend of overuse of PPIs [27][28][29][30][31]. A similar pattern has been observed in Saudi Arabia [32,33].…”
Section: Discussionsupporting
confidence: 63%
“…Using large-scale cohort data of generally healthy individuals in Japan, our study clearly showed a marked increase in PPI use in Japan, which is accompanied by a gradual decrease in H 2 RA use. The increasing and frequent use of PPIs has been reported in many countries such as the United States [31], France [32], Hungary [23], and Iceland [21]. In comparison with Western countries, the percentage of PPI users is still lower in Japan, but the monotonous increase and PPI use of more than 5% in a generally healthy population are noteworthy trends in Japan (Fig 1).…”
Section: Discussionmentioning
confidence: 96%
“…Although several studies have indicated the risk of long-term PPI use [18,19], increasing PPI usage has been reported in various regions of the world [20][21][22][23]. However, information regarding PPI use in East Asia is currently inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Hungary revealed that the average age of PPI users was 65 years old, with a minimum treatment interval of six months. One-fifth of the population had extended use for more than five years [ 14 ]. Patients usually do not self-deprescribe, and most primary care physicians tended to continue the same treatment without reevaluation for the need for PPIs [ 15 ].…”
Section: Reviewmentioning
confidence: 99%